The association between ambient air pollution and the risk of incident nasopharyngeal carcinoma in Hangzhou, China - Zesheng Chen; Zongxue Cheng; Yaoyao Wu; Zhecong Yu; Kang Qin; Caixia Jiang; Jue Xu (Scientific Reports)
Abstract Ambient air pollution exposure was associated with an increased risk of incident cancer, but few previous studies have focused on the associations between ambient air pollution and nasopharyngeal carcinoma (NPC). Thus, our goal is to examine whether exposure to ambient air pollution in Hangzhou, which includes sulfur dioxide (SO2), nitrogen dioxide (NO2), and inhalable particles (PM10), will have an impact the risk of incident cancer. We collected data on daily ambient air pollution data, climate, and daily incidence of NPC in Hangzhou from Jan 1, 2013, to Dec 31, 2022. We applied a generalized additive model (GAM) based on the Poisson distribution to investigate the effect of ambient air pollution on the risk of incident NPC. The effects of ambient air pollution exposure on NPC were also discussed in subgroups by age, gender, region, and season. A total of 3121 NPC incident cases were included during the study period. We discovered that the risk of incident NPC was increased by 0.75% (95% CI: 0.01–1.58), 0.36% (95% CI: 0.03–0.69), and 0.14% (95% CI: 0.01–0.28) for every 1 μg/m3 increase in the concentration of SO2, NO2, and PM10, respectively. These pollutants continued to have a substantial impact on the risk of incident NPC even after controlling for other ambient air pollutants. A noteworthy affirmative connection was a significant positive correlation between SO2 and NPC in male, warm season, urban areas, and elderly subgroups. In contrast to SO2, there was a significant positive correlation between PM10 and NPC in female, warm season, rural areas, non-elderly, and elderly subgroups. The association between NO2 and NPC was significantly positively correlated in male, female, rural areas, and elderly subgroups. In conclusion, our study’s findings demonstrated that exposure to airborne SO2, NO2, and PM10 can negatively impact the risk of incident NPC.